2020
DOI: 10.1007/s10494-020-00159-5
|View full text |Cite
|
Sign up to set email alerts
|

The Eulerian Stochastic Fields Method Applied to Large Eddy Simulations of a Piloted Flame with Inhomogeneous Inlet

Abstract: Large Eddy Simulations of the Sydney mixed-mode flame with inhomogeneous inlet (FJ200-5GP-Lr75-57) are performed using the Eulerian Stochastic Fields (ESF) transported probability functions method to account for the sub-grid scale turbulence–chemistry interaction, to demonstrate the suitability of the ESF method for mixed-mode combustion. An analytically reduced 19-species methane mechanism is used for the description of the chemical reactions. Prior to the reactive case, simulation results of the non-reactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Luo et al (2020) applied a dynamic second-order moment closure model to LES and found that the premixed flame is dominant upstream, causing 70 % of the heat release, which then decreases to about 40 % downstream, with an overall good agreement with measurements. Hansinger et al (2020) performed LES with the Eulerian Stochastic Fields Method and assessed the influence of the number of stochastic fields on the quality of the simulation results. Shrotriya et al (2020) conducted LES with reaction diffusion manifolds (REDIM) because it is mostly independent of the combustion regime.…”
Section: Introductionmentioning
confidence: 99%
“…Luo et al (2020) applied a dynamic second-order moment closure model to LES and found that the premixed flame is dominant upstream, causing 70 % of the heat release, which then decreases to about 40 % downstream, with an overall good agreement with measurements. Hansinger et al (2020) performed LES with the Eulerian Stochastic Fields Method and assessed the influence of the number of stochastic fields on the quality of the simulation results. Shrotriya et al (2020) conducted LES with reaction diffusion manifolds (REDIM) because it is mostly independent of the combustion regime.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the number of stochastic fields has the benefit of shifting the profiles towards the experimental values in the fuel core. However, further increasing N to 16 or 64 does not seem to improve the accuracy significantly, as observed by Hansinger et al (2020). While a single field (N = 1) might be the preferred option when using the ESF with finite rate chemistry (Breda et al 2020;Hansinger et al 2020), the use of N = 8 in this investigation does not increase significantly the computational cost, since the ESF are coupled with tabulated chemistry.…”
Section: Number Of Stochastic Fieldsmentioning
confidence: 74%
“…On the RHS of the equation, the scalar conditioned velocity fluctuations on the sub-grid level have been modelled using the gradient flux hypothesis. The Schmidt numbers Sc, Sc sgs have been assigned equal to 0.7 according to previous investigations (Breda et al 2020;Hansinger et al 2020). Equal diffusivities have been assumed, using unity Lewis numbers.…”
Section: Filtered Density Functionmentioning
confidence: 99%
See 2 more Smart Citations